Manipulating Endoplasmic Reticulum-Plasma Membrane Tethering in Plants Through Fluorescent Protein Complementation - Tao, Kai; Waletich, Justin R.; Arredondo, Felipe; Tyler, Brett M. (Frontiers in Plant Science, 2019)
The bimolecular fluorescence complementation (BiFC) assay has been widely used to examine interactions between integral and peripheral proteins within putative plasma membrane (PM) microdomains. In the course of using BiFC assays to examine the co-localization of plasma membrane (PM) targeted receptor-like kinases (RLKs), such as FLS2, with PM micro-domain proteins such as remorins, we unexpectedly observed heterogeneous distribution patterns of fluorescence on the PM of Nicotiana benthamiana leaf cortical cells. These patterns appeared to co-localize with the endoplasmic reticulum (ER) and with ER-PM contact sites, and closely resembled patterns caused by over-expression of the ER-PM tether protein Synaptotagmin1 (SYT1). Using domain swap experiments with SYT1, we inferred that non-specific dimerization between FLS2-VenusN and VenusC-StRem1.3 could create artificial ER-PM tether proteins analogous to SYT1. The same patterns of ER-PM tethering were produced when a representative set of integral membrane proteins were partnered in BiFC complexes with PM-targeted peripheral membrane proteins, including PtdIns(4)P-binding proteins. We inferred that spontaneous formation of mature fluorescent proteins caused the BiFC complexes to trap the integral membrane proteins in the ER during delivery to the PM, producing a PM-ER tether. This phenomenon could be a useful tool to deliberately manipulate ER-PM tethering or to test protein membrane localization. However, this study also highlights the risk of using the BiFC assay to study membrane protein interactions in plants, due to the possibility of alterations in cellular structures and membrane organization, or misinterpretation of protein-protein interactions. A number of published studies using this approach may therefore need to be revisited.